Toward the formation of a companion animal parasite council for the tropics (CAPCT) - Traub, Rebecca J.; Irwin, Peter; Torres, Filipe Dantas; Tort, Gabriela Pérez; Labarthe, Norma Vollmer; Inpankaew, Tawin; Gatne, Mukulesh; Linh, Bui Khanh; Schwan, Volker; Watanabe, Malaika; Siebert, Susanne; Mencke, Norbert; et al. (BioMed Central, 2015)
This letter advises the imminent formation of the Companion Animal Parasites Council for the Tropics (CAPCT). The CAPCT consists of region-specific (e.g., Asia-Pacific, Latin America and Caribbean, Africa) experts comprising academics, veterinarians, parasitologists, physicians and allied industry partners that will work together to inform, guide and develop best-practice recommendations for the optimal diagnosis, treatment and control of companion animal parasites in the tropics, with the aim of protecting the health of pets and that of the public.